TRANSPORT AND TELECOMMUNICATION OF THE USA - Ahmedov Azimjon; Maxamatdamonov Ilyosbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Transportation in the United States is a crucial aspect of daily life, allowing people and goods to move effectively and efficiently across the vast expanse of the country. From cars and trucks to trains, buses, and airplanes, the United States has an extensive transport infrastructure that plays a critical role in the country’s economic growth and social connectivity.